2021
DOI: 10.3390/biomedicines9121793
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Prohibitin in the Rat Heart Mitochondria in Heart Failure

Abstract: Mitochondria are considered the main organelles in the cell. They play an important role in both normal and abnormal heart function. There is a supramolecular organization between the complexes of the respiratory chain (supercomplexes (SCs)), which are involved in mitochondrial respiration. Prohibitins (PHBs) participate in the regulation of oxidative phosphorylation (OXPHOS) activity and interact with some subunits of the OXPHOS complexes. In this study, we identified a protein whose level was decreased in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Therefore, it is natural to consider antioxidants among possible agents of therapeutic influence. Studies conducted in our laboratory have shown that astaxanthin (AX) is able to have a protective effect on mitochondria in pathologies of the cardiovascular system [ 20 , 22 ]. In addition, the investigations of some researchers demonstrate the suppressive effect of AX on alcohol-induced disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is natural to consider antioxidants among possible agents of therapeutic influence. Studies conducted in our laboratory have shown that astaxanthin (AX) is able to have a protective effect on mitochondria in pathologies of the cardiovascular system [ 20 , 22 ]. In addition, the investigations of some researchers demonstrate the suppressive effect of AX on alcohol-induced disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was shown that AX has a protective effect on the rat heart mitochondria in conditions of heart failure [ 20 , 21 , 22 ]. There was an improvement in mitochondrial functions, an increase in the activity of respiratory chain complexes, and inhibition of the opening of a mitochondrial non-specific pore (mitochondrial permeability transition pore, mPTP).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial fragmentation during apoptosis is considered to be an irreversible signal in the death cascade (Green and Kroemer, 2004). Various diseases associated with heart failure, neurodegeneration, autoimmune and viral infections are mediated by mitochondria-mediated apoptosis (Schneider et al, 2019;Faccenda and Campanella, 2020;Baburina et al, 2021;Steudler et al, 2022). Programmed cell death or apoptosis is a cellular selfdestruction mechanism involving multiple biological events.…”
Section: Mitochondria-mediated Apoptosismentioning
confidence: 99%
“…Keap1 is a substrate adaptor protein for the Cul3-based E3-ligase complex and is involved in ubiquitination via the ubiquitin-proteasome system [20]. However, the cellular stress induced by ROS, xenobiotics, and other electrophiles prevents Nrf2 from interacting with the ubiquitin-conjugating system due to a conformational modification in the E3-ligase complex [21]. After release, Nrf2 translocates into the nucleus, forming a heterodimer with sMaf protein and leading to ARE binding.…”
mentioning
confidence: 99%
“…This Special Issue, entitled "Bioantioxidants in Health and Disease: Chemical, Biological and Biomedical Aspects", which includes original research articles and review articles, shares insights on the redox signaling pathways in different diseases. The study by Baburina et al [21] documented the role of prohibitins in regulating oxidative phosphorylation. Prohibitin forms a complex with mitochondrial membrane proteins and some subunits of the respiratory chain complex.…”
mentioning
confidence: 99%